Lipoxin A4 Attenuates Cell Invasion by Inhibiting ROS/ERK/MMP Pathway in Pancreatic Cancer. (16th November 2015) - Zong, Liang; Li, Jiahui; Chen, Xin; Chen, Ke; Li, Wei; Li, Xuqi; Zhang, Lun; Duan, Wanxing; Lei, Jianjun; Xu, Qinhong; Shan, Tao; Ma, Qingyong; et al.
Abstract : Lipoxin A4 (LXA4 ), an endogenous arachidonic acid metabolite, was previously considered an anti-inflammatory lipid mediator. But it also has the potential to inhibit cancer progression. To explore the therapeutic effect of LXA4 in pancreatic cancer, we used Panc-1 cells to investigate the mechanism by which LXA4 can attenuate pancreatic cancer cell invasion. Our data showed that LXA4 significantly inhibited both cell invasion and the expression of matrix metalloproteinase- (MMP-) 9 and MMP-2. Further experiments implied that LXA4 decreased the levels of intracellular reactive oxygen species (ROS) and the activity of the extracellular signal regulated kinases (ERK) pathway to achieve similar outcome to ROS scavenger N-acetyl-l -cysteine (NAC). However, a decreased level of intracellular ROS was not observed in cells treated with the specific ERK pathway inhibitor FR180204. The blocking of either intracellular ROS or ERK pathway caused the downregulation of MMP-9 and MMP-2 expression. Furthermore, tests revealed that LXA4 inhibited MMP-9 and MMP-2 at the mRNA, protein, and functional levels. Finally, LXA4 dramatically limited the invasion of CoCl2 -mimic hypoxic cells and abrogated intracellular ROS levels, ERK activity, and MMPs expression. These results suggest that LXA4 attenuates cell invasion in pancreatic cancer by suppressing the ROS/ERK/MMPs pathway, which may be beneficial for preventing the invasion of pancreatic cancer.